Knowledge capability and fraud risk assessment in Nigeria deposit money banks: The mediating effect of problem representation - Olusoji Olumide Odukoya; Rose Shamsiah Samsudin (Cogent Business & Management, 2021)
Nigeria Deposit Insurance Corporation (NDIC) annual reports (2014-2017) suggest that the country's deposit money banks (DMBs) have been exposed to escalating incidence of fraud and forgeries. This has hampered their capacity, efficiency and contribution to national economic growth and development. This study examines the capability and competence of DMB regulators to prevent and detect fraud and, at the same time, develop an effective mechanism to do so. The study employed quantitative methodology. Data was collected using questionnaires administered on 350 forensic accountants and bank examiners working with the Central Bank of Nigeria (CBN), NDIC and 15 randomly selected DMBs in Lagos. Data collected were analyzed using descriptive statistics and multivariate regression. Key results include significant positive relationship between the study variables and reduction in fraud incidence in DMBs. This result has implications for existing accounting literature on knowledge capability and competence as vehicles for fraud prevention and detection in DMBs in Nigeria. The study recommends an integrative approach to bank examination in which both forensic accountants and bank examiners are involved as permanent fixtures in fraud prevention and detection in DMBs. This will guarantee a fraud-free DMB sector.
Keywords: 650; Forensic accountants; bank examiners; knowledge capability; problemrepresentation; fraud risk assessment; Nigeria deposit money banks